Tindakan Kolektif Animal Welfare Organizations (AWOS) untuk Mengakhiri Perdagangan Daging Anjing di Pasar Tomohon dari Perspektif New Institutionalism in Economic Sociology (NIES) - Brigitha Prizelia Nanga; Nadia Yovani (CV. Syntax Corporation Indonesia, 2022)
Dog meat is one of the commodities traded in the Tomohon Market. The dog meat trade that had been going on for years there was then met with disapproval from animal welfare organizations (AWO), who took collective action at the policy level with interest in ending the activity. This article aims to explain two things. First, the context of the Minahasa community where the dog meat trade developed and its links. Second, the process and results of the collective action of AWOs at the policy level in response to the dog meat trade. This discussion uses the NIES (New Institutionalism In Economic Sociology) approach from Victor Nee. At the same time, this type of research is qualitative research with a case study strategy. Based on the study results, it can be concluded that the collective action of AWOs supported by informal monitoring mechanisms is a form of response and support for the macrostructure of animal welfare. This effort was hampered and facilitated by different institutional elements. AWOs have not succeeded in realizing their interests but have pushed for alternative policies that refer to rabies regulations targeted at weakening points in the dog meat trade chain